The COCHRANE COLLABORATION: a prime source of evidence-based answers to oral healthcare questions - Zbys Fedorowicz; Trent L Outhouse (Universidade Estadual de Campinas, 2015)
The Cochrane Collaboration [www.cochrane.org] is an international, non-profit, organisation that was established to ensure the worldwide availability of up-to-date and accurate information about the effects of healthcare interventions. It produces and disseminates systematic reviews of healthcare interventions, and promotes the search for evidence in the form of clinical trials and other studies of the effects of interventions.